No home court advantage: The trump impeachment trial and attitudes toward the U.S. Supreme Court - Miles T Armaly; Adam M Enders (Research & Politics)
Although the U.S. Supreme Court goes to great lengths to avoid the “political thicket,” it is sometimes unwittingly pulled in. We employ several experimental treatments—each of which is composed of real behaviors that took place during the Trump impeachment trial—to understand the impact of the trial on attitudes about the Court. We find that Chief Justice Roberts’ presence and behaviors during the trial failed to legitimize the proceeding and may have even harmed views of the Court. Treatments involving Roberts’ actions decreased willingness to accept Court decisions and, in some cases, negatively impacted perceived legitimacy. We also find that criticisms of the Chief Justice by Senators decreased decision acceptance. These findings clarify both the bounds of the institution’s legitimizing power and the tenuous nature of public support in times of greater Court politicization by outside actors.